Metal-Based G-Quadruplex Binders for Cancer Theranostics - Palma, Elisa (Pharmaceuticals (Basel), 2021)
The ability of fluorescent small molecules, such as metal complexes, to selectively recognize G-quadruplex (G4) structures has opened a route to develop new probes for the visualization of these DNA structures in cells. The main goal of this review is to update the most recent research efforts towards the development of novel cancer theranostic agents using this type of metal-based probes that specifically recognize G4 structures. This encompassed a comprehensive overview of the most significant progress in the field, namely based on complexes with Cu, Pt, and Ru that are among the most studied metals to obtain this class of molecules. It is also discussed the potential interest of obtaining G4-binders with medical radiometals (e.g., (99m)Tc, (111)In, (64)Cu, (195m)Pt) suitable for diagnostic and/or therapeutic applications within nuclear medicine modalities, in order to enable their theranostic potential.